Ordered mesoporous silica incorporating platinum nanoparticles as electrode material for paracetamol detection - Thi Thanh Hien NGO; Ioana Carmen FORT; Thanh Huyen PHAM; Graziella Liana TURDEAN (My University, 2021)
Ordered mesoporous silica incorporating platinum nanoparticles as electrode material for paracetamol detection
Keywords: Ordered mesoporous silica